“BERTAHAN DI MASA SULIT” (MOTIVASI DRIVER TAKSI KONVENSIONAL KOPTAX NGURAH RAI DI TENGAH GENCARNYA TRANSPORTASI ONLINE) - ADELIYA PUSPITA DEWI; ANAK AGUNG NGURAH OKA SURYADINATHA GORDA (GANEC SWARA, 2024)
The emergence of online transportation, especially online taxis, has created intense competition between conventional taxis and online taxis which has a direct impact on drivers. To survive at work in the current era, motivation is needed that can encourage conventional taxi drivers to persist in their work amidst the dilemma of the advantages and disadvantages of being a conventional taxi driver. This research aims to determine the motivation for staying with conventional taxi drivers in one of the taxi cooperative organizations in Bali, namely Koptax Ngurah Rai. This research uses qualitative and quantitative data types, using data collection techniques through interviews, observation, and documentation processes. Primary data was obtained through interviews and direct observation with Koptax Ngurah Rai conventional taxi drivers to determine the drivers' motivation to survive. Secondary data in this research is in the form of literary studies such as theory and previous research related to the research discussion. Based on the analysis of the data from this. research, it can be concluded that the motivation for staying with Koptax Ngurah Rai conventional taxi drivers is due to the need, encouragement, and goals to be achieved. From the results of the research, it was found that the motivation to persist in one's job as a conventional taxi driver comes from within the taxi driver (intrinsic), such as the need for income, lack of competence, a feeling of gratitude and there is something that comes from outside the taxi driver (extrinsic), such as the existence of organizational assistance in terms of licensing taxi vehicles.